382 Comparison of the efficacy of reiki versus sport as supportive care during neoadjuvant chemotherapy of early breast cancer: sub analysis of the randomized controlled reassure (Reiki as supportive treatment during chemotherapy of breast cancer) study. (4th December 2020) - Zander, Lena; Haunreiter, Lisa; Katzendobler, Sophie; Schmidt, Rosemarie; Napieralski, Rudolf; Petri, Isabella; Andrulat, Anne; Münch, Katrin; Hanusch, Claus; Braun, Michael; Kiechle, Marion; Ettl, Johannes
Abstract : Introduction/Background: Breast cancer is the most common cancer of the female, and the second most common cancer overall. While chemotherapy is standard of care for many patients with this type of cancer, it is associated with various side effects that require supportive care. In addition to standard medical therapies, patients may benefit from complementary treatments, such as sport therapy or Reiki. Reiki is a far eastern method that promotes healing on a physical, mental and emotional level and activates self-healing powers. Aim of this study was to compare the efficacy of Reiki versus Sport as supportive care during primary systemic therapy of early breast cancer within the REASSURE study. Methodology: REASSURE was a prospective, randomized, controlled, two-armed clinical trial, in which patients with breast cancer received chemotherapy and Reiki (18 times) or chemotherapy and sport (18 times). This evaluation specifically focused on patients who received neoadjuvant chemotherapy with four cycles of Epirubicin and Cyclophosphamide followed by 12 cycles of a Taxane. All patients were enrolled in the REASSURE-study and randomized before their first chemotherapy cycle. While sport therapy was delivered as conventional physiotherapy, Reiki was delivered by a trained Reiki practitioner. We conducted a statistical analysis using Wilcoxon Rank sum tests to compare incidence of adverse events (febrile neutropenia (FNP), fever, infection, blood count variation, hospitalization), dose modifications (therapy discontinuation, dose interruption, dose reduction) and use of conventional medical supportive care treatments (G-CSF, antibiotics, blood transfusion, platelet transfusion). Results: A total of 48 subjects were included, of which 27 received Reiki and 21 received sport treatment. When comparing FNP events between both groups, we found 3 events in the sport group, whereas there were none in the Reiki group (p = 0.047). The median number of GCSF-application was 4 (range 0 to 8) in the sport group versus 0 (range 0 to 8) in the Reiki group (p = 0.006). For all other parameters, calculation of 95 percent confidence intervals showed no clinically significant difference between the two groups. Conclusion: Reiki may pose a viable alternative medical treatment option to sport as a supportive therapy option to combat side effects of neoadjuvant Epirubicin, Cyclophosphamide and Taxane chemotherapy for breast cancer treatment. To better understand the beneficial influence of this therapy, further research is needed to compare Reiki with a control group receiving no additional therapy. Disclosures: REASSURE Studie - This study is a collaborative study between Frauenklinik Rechts der Isar, Frauenklinik des Rotkreuzklinikums, Frauenklinik der München Klinik Harlaching, and ProReiki – Berufsverband e.V.. There was no funding. There are no conflicts of interest.